The German economy in 1982 and beyond - Dieter Wermuth (Intereconomics, 1982)
The Federal Republic of Germany is presently experiencing the deepest and longest recession in its history. The situation is characterised by high and rising unemployment figures, slowing growth, a steep increase in the number of bankruptcies in the business sector as well as by a rapidly rising public sector deficit. They key to any solution, Dr. Wermuth argues, is held by the German monetary authorities more than by anyone else.
Keywords: 330; Economic Trends